KELEMBAGAAN KELOMPOK TANI HUTAN PROGRAM PENDAMPINGAN SCBFWM DISEKITAR SUB DAERAH ALIRAN SUNGAI MIU (KASUS DESA PAKULI KECAMATAN GUMBASA KABUPATEN SIGI) - Sari, Novita; Golar, Golar; Toknok, Bau (Universitas Tadulako, 2013)
This research aimed to know form of the farmers group organization in Pakuli village and determine the problems that faced by them in Pakuli village, Gumbasa district, Sigi regency, Central Sulawesi. Data was collected by using questionnair and in-depth interviews on respondents. The total number of respondents were twenty five. Theres pondents were selected by using purposive sampling method with qualitative descriptive analysis. The results showed that form of the farmer group organization in Pakuli village was a formal organization and it is exist before SCBFWM programs were introduced and implemented in this area. Hence, organization problems that causes farmers group go out from SCBFWM supervising were imbalance of actions, leadership and social gaps. Keywords: Organization form, farmers group, SCBFMW